Penggunaan Media Stiky Wall Tematik Dalam Meningkatkan Kemampuan Bahasa Ekspresif Kelompok B di RA Dzikrurrahman Karawang - Azzahra, Aprilia Fatimah; Aisyah, Dewi Siti; Putri, Feronica Eka (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to describe the methods and results of learning carried out using thematic wall-mounted media to improve children's expressive language skills. This research was conducted at RA Dzikrurrahman Karawang in August 2023 with research subjects totaling 9 children from group B. The research method used was classroom action research following the Kemmis and McTaggart approach, which involved the steps of planning, implementing actions, observing and reflecting. . This research consisted of two cycles, with the first cycle involving 6 meetings and the second cycle involving 2 meetings. Data is collected through various techniques, including tests, observation, interviews, and documentation. Data analysis was carried out quantitatively to measure the level of success and qualitatively to explain the research results. The results of the study showed a significant increase in children's expressive language abilities after using thematic wall-mounted media. The percentage of success before the action was 32%, increased to 55% in cycle I, and reached 79% in cycle II. Thus, it can be concluded that the use of thematic wall-mounted media has a positive impact on the expressive language skills of children aged 5-6 years.